The Dual Burden of Malnutrition in Brazil Among Children 4–13.9 Years of Age. (29th May 2020) - Anater, Andrea; Mathias, Kevin; Hampton, Joel; Eldridge, Alison; Campos, Vanessa
Abstract: Objectives: To evaluate the prevalence of underweight, overweight and obesity among children aged 4 to 13.9 years in Brazil. Methods: Caregivers of a cross-sectional random sample of children aged 4–13.9 years ( n  = 970) identified in three census regions in Brazil were surveyed. Children's body weight and height were measured using a calibrated scale and a stadiometer following U.S. Centers for Disease Prevention and Control procedures. Reference cut-points generated from a previous sample of Brazilian children using the LMS method to calculated sex specific BMI growth curves that intersected BMIs of 17.5, 25 and 30, at 20 years of age, were used to define underweight, overweight and obese children, respectively. Results: Among older children, the prevalence of underweight and obesity decreased while overweight remained relatively stable across all age groups. The percentage (% ± SE) for underweight, overweight, and obese among 4–6.9 year olds ( n  = 319) were 5.7 ± 1%, 36 ± 4%, and 17 ± 3%, respectively. For 7–10.9 year olds ( n  = 396), these percentages were 3.1 ± 1%, 38 ± 3%, and 13 ± 2%; and for 11–13.9 year olds ( n  = 255), 3.2 ± 2%, 37 ± 5%, and 10 ± 3%. The overall percentage of underweight, overweight, and obese for males ( n  = 508) were 2.8 ± 1%, 34 ± 3%, and 11 ± 2%; and for females ( n  = 462), 4.9 ± 1%, 40 ± 3%, and 16 ± 2%. The prevalence of malnutrition among females was higher than for males for each condition and across all age categories except among 7–10.9 year olds with overnutrition. Conclusions: Brazil is a middle-income country undergoing a rapid nutrition transition. A shift in dietary patterns and consumption and energy expenditures can result in the double burden of malnutrition, characterized by the coexistence of undernutrition and overweight and obesity within the population. Both are serious health problems, particularly when they occur in childhood as the effects can linger into adulthood. In 2019, the prevalence of overweight and obesity remain elevated, as does underweight, particularly among females. Promotion of physical activity and encouraging healthy dietary habits are needed to curtail obesity and overweight rates, with poverty reduction efforts enhanced to address the prevalence of underweight children. Funding Sources: This project was funded by Nestlé Research, Vers-chez-les-Blanc, Lausanne, Switzerland.